MiR-26a-5p suppresses nasopharyngeal carcinoma progression by inhibiting PTGS2 expression. Issue 6 (19th March 2022) - Cai, Binlin; Qu, Xiu; Kan, Dan; Luo, Yi
ABSTRACT: Nasopharyngeal carcinoma (NPC) has a low five-year survival rate, and its pathogenesis remains unclear. There is an urgent need to improve our understanding of the genetic regulation of NPC tumorigenesis and development. The role of miR-26a-5p in NPC growth regulation and the expression of its target, PTGS2, was analyzed. Quantitative Real-time PCR assay was used to detect miR-26a-5p and PTGS2 expression in human NPC tissues and cell lines. The RNA pull-down dual-luciferase reporter assay was used to determine the association between miR-26a-5p and PTGS2. The effects of miR-26a-5p and PTGS2 on NPC cell viability, proliferation, migration, and invasion were measured by CCK-8, BrdU, and Transwell assays. miR-26a-5p expression in NPC tissues and cell lines was significantly decreased. The overexpression of miR-26a-5p inhibited the viability, proliferation, migration, and invasion of NPC cells. miR-26a-5p bound to the 3-ʹuntranslated region of PTGS2, thus reducing PTGS2 protein levels. miR-26a-5p inhibited NPC development by reducing the expression of its target PTGS2.